Concern about threatened species and ecosystem disservices underpin public willingness to pay for ecological restoration. Issue 3 (9th November 2018) - Wilson, Kerrie A.; Davis, Katrina J.; Matzek, Virginia; Kragt, Marit E.
Abstract : Public preferences for ecological restoration can be revealed through environmental valuation studies that aim to measure willingness to pay. However, respondents' environmental views will often influence the conclusions drawn from such studies. We conducted a national survey of perceptions of the benefits and perverse outcomes arising from ecological restoration using a dichotomous choice payment card. Using interval regression to estimate willingness to pay, we find that there are respondents who will perceive mostly biodiversity benefits from restoration, with a particular interest in threatened species recovery. We find that this eco‐centric view of the benefits of restoration also increases the dollar amount that respondents are willing to pay to support restoration activities. A proportion of respondents also perceive restoration as having negative impacts, with concerns orientated towards increased fire, decreased farmland productivity, and groundwater availability. Perceptions of the potential effects of restoration on land productivity had a significant negative influence on the amount of money respondents were willing to pay. These findings are useful for targeting outreach in order to garner public support for ecological restoration.